Integration Of Traditional Culture Village Values For Character Education At Elementary School In Indonesia - Sutinah,; Wasita Aji, Styo Mahendra; Jumardin, (International Conference on Elementary Education, 2025)
This article aims to find a pattern of integrating the cultural values of traditional villages (kampung adat) for character education in elementary schools. Indonesia, as a nation with one of the largest ethnic groups in the world, has character values that become cultural characteristics that continue to be inherited. Conserved characters in traditional villages can survive various challenges. The values of traditional villages can be explored as character value patterns for early formal education, namely elementary schools. The method of writing this article is a literature review. Data collection by collecting articles from the Google Scholar database in the last 5 years, books, and other relevant literature. Data is analyzed descriptively and qualitatively. The article's results focus on the values of traditional villages in Indonesia and the Integration of Traditional Village Values in Elementary School Character Education. Finally, the values of the conserved traditional villages can be the capital for building character education in elementary education.